2016
DOI: 10.1182/blood-2015-09-672303
|View full text |Cite
|
Sign up to set email alerts
|

Ranking reactive glutamines in the fibrinogen αC region that are targeted by blood coagulant factor XIII

Abstract: Key Points• FXIIIa exhibits a preference for Q237 in crosslinking reactions within fibrinogen aC (233-425) followed by Q328 and Q366.• None of the reactive glutamines in aC 233-425 (Q237, Q328, and Q366) are required to react first before the others can crosslink.Factor XIIIa (FXIIIa) introduces covalent g-glutamyl-«-lysyl crosslinks into the blood clot network. These crosslinks involve both the g and a chains of fibrin. The C-terminal portion of the fibrin a chain extends into the aC region (210-610). Crossli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(49 citation statements)
references
References 61 publications
1
48
0
Order By: Relevance
“…Proteolysis of fibrinogen by GoF ADAMTS‐13 removes the α‐chain residues 241–476 and 518–584 (Fig. 2C), which are required for α‐chain association 34.…”
Section: Discussionmentioning
confidence: 99%
“…Proteolysis of fibrinogen by GoF ADAMTS‐13 removes the α‐chain residues 241–476 and 518–584 (Fig. 2C), which are required for α‐chain association 34.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study (Chapter 3), a mass spectrometry and a complementary NMR spectroscopy assay were developed to monitor and rank the extent of crosslinking for three known reactive glutamines (Q237, Q366, and Q328) within a segment of the αC region (αC 233-425). 108 Fbg αC (233-425) was previously used to localize and characterize a Factor XIII binding site within the fibrinogen Aα chain. 72 A residue within this αC region, Aα E396, was identified to be critical for the binding of Factor XIII.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, research findings have suggested that the alpha chain of fibrinogen contributes unique roles to the overall clot structure and stability. 86,108,109 The main focus of this dissertation has been to understand fibrin crosslinking at a molecular level.…”
Section: Research Summary and Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations